Human adaptation to immobilization: Novel insights of impacts on glucose disposal and fuel utilization. Issue 6 (4th September 2022) - Shur, Natalie F.; Simpson, Elizabeth J.; Crossland, Hannah; Chivaka, Prince K.; Constantin, Despina; Cordon, Sally M.; Constantin‐Teodosiu, Dumitru; Stephens, Francis B.; Lobo, Dileep N.; Szewczyk, Nate; Narici, Marco; Prats, Clara; et al.
Abstract: Background: Bed rest (BR) reduces whole‐body insulin‐stimulated glucose disposal (GD) and alters muscle fuel metabolism, but little is known about metabolic adaptation from acute to chronic BR nor the mechanisms involved, particularly when volunteers are maintained in energy balance. Methods: Healthy males ( n = 10, 24.0 ± 1.3 years), maintained in energy balance, underwent 3‐day BR (acute BR). A second cohort matched for sex and body mass index ( n = 20, 34.2 ± 1.8 years) underwent 56‐day BR (chronic BR). A hyperinsulinaemic euglycaemic clamp (60 mU/m 2 /min) was performed to determine rates of whole‐body insulin‐stimulated GD before and after BR (normalized to lean body mass). Indirect calorimetry was performed before and during steady state of each clamp to calculate rates of whole‐body fuel oxidation. Muscle biopsies were taken to determine muscle glycogen, metabolite and intramyocellular lipid (IMCL) contents, and the expression of 191 mRNA targets before and after BR. Two‐way repeated measures analysis of variance was used to detect differences in endpoint measures. Results: Acute BR reduced insulin‐mediated GD (Pre 11.5 ± 0.7 vs. Post 9.3 ± 0.6 mg/kg/min, P < 0.001), which was unchanged in magnitude following chronic BR (Pre 10.2 ± 0.4 vs. Post 7.9 ± 0.3 mg/kg/min, P < 0.05). This reduction in GD was paralleled by the elimination of the 35% increase in insulin‐stimulated muscle glycogen storage following both acute and chronic BR. Acute BR had no impact on insulin‐stimulated carbohydrate (CHO; Pre 3.69 ± 0.39 vs. Post 4.34 ± 0.22 mg/kg/min) and lipid (Pre 1.13 ± 0.14 vs. Post 0.59 ± 0.11 mg/kg/min) oxidation, but chronic BR reduced CHO oxidation (Pre 3.34 ± 0.18 vs. Post 2.72 ± 0.13 mg/kg/min, P < 0.05) and blunted the magnitude of insulin‐mediated inhibition of lipid oxidation (Pre 0.60 ± 0.07 vs. Post 0.85 ± 0.06 mg/kg/min, P < 0.05). Neither acute nor chronic BR increased muscle IMCL content. Plentiful mRNA abundance changes were detected following acute BR, which waned following chronic BR and reflected changes in fuel oxidation and muscle glycogen storage at this time point. Conclusions: Acute BR suppressed insulin‐stimulated GD and storage, but the extent of this suppression increased no further in chronic BR. However, insulin‐mediated inhibition of fat oxidation after chronic BR was less than acute BR and was accompanied by blunted CHO oxidation. The juxtaposition of these responses shows that the regulation of GD and storage can be dissociated from substrate oxidation. Additionally, the shift in substrate oxidation after chronic BR was not explained by IMCL accumulation but reflected by muscle mRNA and pyruvate dehydrogenase kinase 4 protein abundance changes, pointing to lack of muscle contraction per se as the primary signal for muscle adaptation.